Big And Small (Level-2) BBC Earth (Activity Book) - "Catrin Morris" (LadyBird Books Limited US, 2019)
Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language. Recommended for children aged 4+, the five levels of Readers and Activity Books follow the CEFR framework (Pre-A1 to A2) and include language activities that help develop key skills and provide preparation for the Cambridge English: Young Learners (YLE) Starters, Movers and Flyers exams.